PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA ROOFTOP KAPASITAS 600 WP ON GRID - Deniarahman, Asrul; Sultan; Nrartha, I Made Ari (Depertment of Electrical Engineering University of Mataram, 2024)
The increasing demand for electric power, along with an economic growth estimated at about 7%-10% per year, means that electricity consumption in Indonesia will rise. As a country with a tropical climate, Indonesia has the potential for renewable energy in the form of solar energy with an average irradiation of 4.5 – 4.8 W/m2. Therefore, the development of solar power plants (PLTS) is highly necessary, leading to the issuance of Ministerial Regulation ESDM Number 26 of 2021, which contains regulations on the installation of rooftop PLTS. This study aims to obtain a 600 Wp capacity on-grid rooftop PLTS system in accordance with Permen ESDM Number 26 of 2021. It also seeks to determine the energy production (kWh/day) and the efficiency of the 600 Wp on-grid rooftop PLTS system. The results obtained from this study include achieving an on-grid rooftop PLTS system with a 600 Wp capacity, obtaining a total production in 1 day over 3 days of 2.3 kWh on day 1, 2.1 kWh on day 2, and 2.2 kWh on day 3. Additionally, the average system efficiency was found to be 9.06% on day 1, 9.12% on day 2, and 8.85% on day 3. These results are based on measurements taken in August, when, according to the solar cycle, the sun is north of the equator, whereas the installation point of the PLTS is in the southern hemisphere.